Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Locus of Control terhadap Perilaku Manajemen Bisnis pada UMKM Parfum Reffil di Kota Jambi - Muhammad Rifkhi; Ahmad Syahrizal; Achyat Budianto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The purpose of this study is 1) to analyze the influence of financial knowledge on business management behavior in refill perfume SMEs in Jambi City. 2) to analyze the influence of financial attitude on business management behavior in refill perfume SMEs in Jambi City. 3) to analyze the influence of locus of control on business management behavior in refill perfume SMEs in Jambi City. 4) to analyze the influence of financial knowledge, financial attitude, and locus of control on business management behavior in refill perfume SMEs in Jambi City. The research method used is quantitative descriptive analysis, with a sample size of 62 respondents from refill perfume businesses in Jambi City, utilizing multiple linear regression analysis. The results show that 1) simultaneously, the variables of financial knowledge, financial attitude, and locus of control have a positive and significant effect on business management behavior. 2) Partially, the variable of financial knowledge has a positive and significant effect on business management behavior. 3) Partially, the variable of financial attitude has a positive and significant effect on business management behavior. 4) Partially, the variable of locus of control has a positive and significant effect on business management behavior.